A Review of Studies of Geomagnetic Storms and Auroral/Magnetospheric Substorms Based on the Electric Current Approach - Akasofu, Syun-Ichi (Frontiers in Astronomy and Space Sciences, 2021)
The progress of space physics is reviewed from my personal point of view, particularly how I have reached my present understanding of auroral substorms and geomagnetic storms from the time of the earliest days of space physics. This review is somewhat unique in two ways. First of all, instead of taking the magnetic field line approach (including magnetic reconnection), I have taken the electric current approach; it consists of power supply (dynamo), transmission (currents/circuits) and dissipation (auroral/magnetospheric substorms).This is the basic way to study electromagnetic phenomena and is much more instructive in understanding the physics involved in the chain processes. Secondly, this is not like a textbook-like review, but it is hoped that my humble experience may be useful to see how a new science of space physics has evolved with a number of controversies. On the other hand, it can be seen that the electric current approach is still in a very rudiment stage. Thus, new generations of researchers are most welcome in taking this new way of studying auroral/magnetospheric substorm and geomagnetic storms.